Maximum Rectilinear Convex Subsets - Perez-Lantero, P (Society for Industrial and Applied Mathematics Publications, 2021)
Let P be a set of n points in the plane. We consider a variation of the classical Erd\H os-Szekeres problem, presenting efficient algorithms with O(n3) running time and O(n2) space complexity that compute (1) a subset S of P such that the boundary of the rectilinear convex hull of S has the maximum number of points from P, (2) a subset S of P such that the boundary of the rectilinear convex hull of S has the maximum number of points from P and its interior contains no element of P, (3) a subset S of P such that the rectilinear convex hull of S has maximum area and its interior contains no element of P, and (4) when each point of P is assigned a weight, positive or negative, a subset S of P that maximizes the total weight of the points in the rectilinear convex hull of S. We also revisit the problems of computing a maximum area orthoconvex polygon and computing a maximum area staircase polygon, amidst a point set in a rectangular domain. We obtain new and simpler algorithms to solve both problems with the same complexity as in the state of the art. © 2021 Society for Industrial and Applied Mathematics Publications. All rights reserved.